Fe-N-C carbon-based catalytic electrode for ink direct-writing 3D printing and electrochemical carbon capture application of Fe-N-C carbon-based catalytic electrode

The preparation of Fe-N-C carbon-based catalytic electrodes through direct ink writing 3D printing technology solves the problem of high cost and inability to customize the existing M-N-C catalytic electrodes, and achieves efficient carbon dioxide electrochemical carbon capture and stability improvement.

CN119913540APending Publication Date: 2025-05-02LANZHOU JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411658914.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The existing M-N-C catalytic electrodes have high costs, shape and structure that cannot be customized in the electrochemical carbon capture concentration of carbon dioxide, which limits its application scope.

Method used

Fe-N-C carbon-based catalytic electrodes are prepared by direct ink writing 3D printing technology. Through pre-carbonization and final carbonization treatment, a catalytic electrode with a porous structure is formed to achieve customization of shape and structure.

Benefits of technology

It realizes efficient electrochemical carbon capture of catalytic electrodes, improves the efficiency and stability of CO Faraday, reduces production costs, and expands the scope of application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005142777910000011
    Figure HDA0005142777910000011
  • Figure HDA0005142777910000012
    Figure HDA0005142777910000012
  • Figure HDA0005142777910000013
    Figure HDA0005142777910000013
Patent Text Reader

Abstract

The invention provides a method for preparing a Fe-N-C carbon-based catalytic electrode by an ink direct writing 3D printing technology (DIW). Specifically, gelatin is added into a buffer solution, a cross-linking agent is added, dialysis and freeze drying are performed to obtain methacrylated gelatin (GelMA), then the GelMA and a photoinitiator are mixed and dissolved in water in proportion, then the mixture and new gelatin are uniformly mixed in water in a specified proportion, ultrasonic treatment is performed to obtain printable ink, and finally, the ink is directly written and printed into various 3D components. The printing precursor is firstly freeze-dried and then subjected to carbonization treatment and active site doping, and finally the ink direct writing 3D printing Fe-N-C carbon-based catalytic electrode is obtained. The 3D carbon-based active electrode in any shape can be constructed, the specification, the shape and other parameters of the electrode can be controlled by adjusting the model parameters of ink direct writing printing, catalytic electrodes needed by various electrochemical devices can be developed based on the printing technology, and the printing technology can be applied to various electro-catalysis chemical engineering fields such as electrochemical carbon capture.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrocatalytic chemical industry and atmospheric low-carbon governance, and specifically relates to an Fe-NC carbon-based catalytic electrode directly written by ink and 3D printed and its application in the "electrochemical carbon capture" process. Background Art

[0002] With the rapid development of industry, a large amount of carbon dioxide gas is emitted, which has caused serious ecological and environmental problems such as greenhouse effect and ocean acidification. At the same time, the energy crisis is becoming increasingly serious, and it is urgent to find alternative energy sources. The carbon dioxide electroreduction process driven by renewable electricity can not only reduce the carbon dioxide content in the atmosphere and solve environmental problems, but also convert carbon dioxide into energy with utilization value, realizing low-cost "electrochemical carbon capture". At present, catalytic materials prepared by precious metals have excellent performance for carbon dioxide "electrochemical carbon capture", but due to the high cost, they do not have a good prospect for large-scale application. Therefore, it is necessary to find an efficient carbon dioxide electroreduction catalytic electrode constructed by non-precious metal elements. The MNC catalytic system prepared using non-precious metal elements is low in cost and has relatively good performance in carbon dioxide electrochemical carbon capture. However, the MNC catalytic electrodes prepared at this stage are generally based on the powder catalyst process, which requires further processing to be used as catalytic electrodes, and the catalytic electrodes prepared cannot achieve high-degree-of-freedom shape and structure customization, which leads to many restrictions on their application.

[0003] In recent years, carbon-based materials have attracted much attention in the field of catalytic materials due to their rich raw materials, acid and alkali resistance, high temperature resistance and environmental friendliness. In particular, the introduction of different heteroatoms into carbon materials can construct a high-performance MNC catalytic system, which can significantly improve the catalytic activity of carbon materials. The MNC carbon material catalytic electrodes prepared by the gel method have been reported to have achieved relatively good application effects such as oxygen reduction and oxygen precipitation. However, these materials are based on the powder process to develop catalytic electrodes. This method cannot achieve customization of the shape of the catalytic electrode, nor can it obtain a complex structure, nor can it further improve the mass transfer and conductivity in the catalytic process by adjusting the catalytic electrode, and its application scope is greatly limited.

[0004] Since the 1980s, 3D printing technology has attracted worldwide attention and has begun to enter people's vision and life. Three-dimensional (3D) printing technology, also known as additive manufacturing (AM) technology, is a layer-by-layer manufacturing technology of three-dimensional (3D) structures derived from computer-aided design (CAD) drawing. 3D printing creates physical objects from geometric representations by adding continuous layers of materials under computer control. Due to its novel molding method, 3D printing provides unlimited possibilities for leapfrog development in many fields.

[0005] Electrocatalytic chemical technology can also benefit from 3D printing technology. 3D printing can facilitate the design and manufacture of more economical and more required electrochemical devices. Among them, ink direct writing 3D printing, as a flexible and powerful technology, is also suitable for the customized development of diversified functional catalytic electrodes. Ink direct writing 3D printing, due to its excellent compatibility, can use a variety of raw materials and can flexibly build catalytic electrodes according to demand. In recent years, the cost of ink direct writing 3D printers and printing materials has been declining. As the most economical 3D printing method, it has unlimited possibilities in industrial applications. It is worth mentioning that ink direct writing 3D printing catalytic electrodes can achieve shape and size control, avoiding the complex manufacturing process required by traditional powder process methods to achieve the same accuracy. However, in the process of printing using this technology, the temperature and concentration of the printing ink, and the thickness of the inner diameter of the extrusion needle will determine whether the target structure can be successfully printed; explore a reasonable active component doping process to achieve electroreduction activity of the printed carbon material, thereby achieving electroreduction carbon fixation, these parameters still need to be further determined. Summary of the invention

[0006] Based on the above problems existing in the prior art, the present invention provides a preparation and application of Fe-NC carbon-based catalytic electrode by ink direct writing 3D printing. The catalytic electrode is simple to prepare, has a unique electrode morphology structure, and has good electrochemical carbon capture performance.

[0007] To achieve the above object, the present invention adopts the following scheme:

[0008] 1. Preparation of Fe-NC carbon-based catalytic electrode by ink direct writing 3D printing

[0009] (1) Prepare ink direct writing ink

[0010] Add gelatin to a buffer solution, then add a cross-linking agent, dialyze, and freeze-dry to obtain GelMA. Mix GelMA and a photoinitiator in water according to a certain proportion until they are completely dissolved. Then mix gelatin and the prepared sample in water according to a certain proportion, sonicate until uniform, and prepare a printable ink, which is then stored away from light.

[0011] The gelatin has the following functions: 1. carbon source; 2. important skeleton component of 3D printed components. The gelatin solution forms a hydrogel after cross-linking, and the water therein serves as a porogen.

[0012] The buffer is one or more of phosphate buffer, glycine-hydrochloric acid buffer, phthalic acid-hydrochloric acid buffer, and the pH of the buffer is between 6.60 and 6.50.

[0013] The cross-linking agent is one or more of dicumyl peroxide (DCP), methacrylic anhydride, and dicumyl hydroperoxide. The amount of the cross-linking agent added is 0.05 to 1.00 times the mass of gelatin.

[0014] The molecular weight cut-off of the dialysis bag used in the dialysis operation is between 1000 and 1500.

[0015] The freeze drying needs to be carried out at -30 to -10°C for 15 to 24 hours.

[0016] The photoinitiator is one or more of diphenylphosphine oxide, benzoin dimethyl ether, and triphenyl hexafluorophosphate hexachloride. The amount of the photoinitiator added is 0.01 to 0.05 times that of GelMA.

[0017] The gelatin and the sample are mixed in a ratio of 2:1.

[0018] The ultrasonic operation needs to be carried out in water at 10-50°C.

[0019] (2) Printing electrode precursor components

[0020] According to the shape required in the electrocatalytic process, the 3D printing ink is 3D printed using ink direct writing technology to obtain a 3D printed body ( Figure 1 a);

[0021] (3) Construction of Fe-NC carbon material catalytic electrode

[0022] The 3D printed body is pre-carbonized to obtain a porous 3D carbon-based electrode. The porous 3D carbon-based electrode is placed in a solution containing active substances and soaked for 1 to 5 hours, and then subjected to a final carbonization treatment to obtain a 3DFe-NC carbon material catalytic electrode ( Figure 1 b).

[0023] The active substance is one or more of iron phthalocyanine, iron acetylacetonate, and iron chloride. The concentration of the solution is in the range of 7 to 10 g L -1 .

[0024] The pre-carbonization treatment process is as follows: in a tubular furnace, the temperature is first raised to 800-1000° C. at a rate of 1-10° C. / min, then kept constant for 1-10 hours, and finally lowered to room temperature at a rate of 1-10° C. / min.

[0025] The final carbonization treatment process is: in a tubular furnace, firstly heating to 800-1000° C. at a rate of 1-10° C. / min, then keeping the temperature constant for 1-10 hours, and finally cooling to room temperature at a rate of 1-10° C. / min.

[0026] 2. Characterization of Ink Direct Writing 3D Printed Fe-NC Carbon-based Catalytic Electrode

[0027] Taking the ink direct writing Fe-NC carbon-based catalytic electrode (DIW-FePc-CE) with iron phthalocyanine as the iron source as an example, this material was characterized by TEM, XRD, and XPS.

[0028] (1) TEM characterization

[0029] TEM images ( Figure 2 ) reveals the morphology of DIW-FePc-CE before and after the carbonization process. Figure 2 As can be seen from a and b, the electrode before carbonization presents a dense structure, and the electrode after carbonization has a clear porous structure, indicating that carbonization transforms the electrode into a porous structure. The porous structure can make the catalytic electrode have more accessible catalytic active sites. This structure also has the advantage of fast mass transfer, which can enable the electrode to reduce the current density in CO2RR applications while showing a higher CO Faraday efficiency (FE CO ).

[0030] (2) XRD characterization

[0031] In order to obtain more information about the catalytic electrode, XRD test was performed on DIW-FePc-CE. Figure 3 The test results are shown in Figure 2. It can be seen that only carbon characteristic peaks exist in the electrode (DIW-CE) without iron phthalocyanine doping, and FePc characteristic peaks appear in the spectrum after doping. The XRD test results prove that the components in the produced electrode are in line with expectations.

[0032] (3) XPS characterization

[0033] Figure 4 is the XPS characterization result, Figure 4 The four peaks on a correspond to CC (284.7 eV), CN (285.1 eV), CO (287.6 eV) and OC=O (292.4 eV), respectively. Figure 4 b shows four peaks of N1s, namely pyridinic N (397.7 eV), pyrrolic N (398.2 eV), graphitic N (401.3 eV), and oxidized N (403.1 eV). Figure 4 c is the XPS spectrum of Fe 2p. The peaks at 710 eV and 724 eV correspond to Fe 2p 3 / 2 and Fe 2p 1 / 2 The peaks at 712eV and 725eV correspond to Fe 2+ The characteristic peaks of 709eV and 723eV correspond to Fe 3+ The characteristic peaks indicate the presence of Fe 2+ , Fe 3+The peaks at 719eV and 731eV are satellite peaks, indicating the presence of impurities in the product. The XPS test results prove that the components present in the produced electrode are in line with expectations.

[0034] 3. Activity test of Fe-NC carbon-based catalytic electrode printed by ink direct writing 3D printing

[0035] In order to illustrate the performance of the prepared ink direct writing 3D printed Fe-NC carbon material catalytic electrode, the activity test was carried out using the DIW-FePc-CE electrode as an example.

[0036] (1) Electrochemical carbon capture performance test

[0037] Figure 5 a is the test result of the catalytic performance of the DIW-FePc-CE electrode prepared in the present invention for reducing CO2 to CO.

[0038] The specific method of the performance detection is to use DIW-FePc-CE electrode as a working electrode, a platinum sheet as a counter electrode, an Ag / AgCl electrode as a reference electrode and a 0.1M KHCO3 solution to construct a three-electrode system to achieve electrochemical carbon capture.

[0039] It can be seen that as the applied voltage increases, the FE of the electrode CO It shows a trend of increasing first and then decreasing. When the applied voltage is -0.7V, the Faraday efficiency of the electrode reaches the highest (FE CO =61%). This indicates that DIW-FePc-CE has good catalytic activity.

[0040] (2) Stability test

[0041] Stability is also one of the important parameters to measure the catalytic performance of the electrode. Therefore, the stability test of DIW-FePc-CE electrode was carried out ( Figure 5 b).

[0042] The specific method of the stability test is that the specific method of the performance test is to construct a three-electrode system with a DIW-FePc-CE electrode as a working electrode, a platinum sheet as a counter electrode, an Ag / AgCl electrode as a reference electrode and a 0.1M KHCO3 solution, and operate for 10 hours at an applied voltage of -0.7V, with sampling once every 1 hour.

[0043] It can be seen that in the whole process co The upward trend H2 The FE CO It is basically stable at about 55%, indicating that the DIW-FePc-CE electrode has good stability.

[0044] Compared with the prior art, the present invention has the following beneficial effects:

[0045] 1. The raw material of the catalytic electrode prepared by the present invention is gel. The gel has the characteristic of being high in water content. After being fully dried, the obtained catalytic electrode finally presents a porous structure, so that it has more accessible catalytic active sites. This structure also has the advantage of fast mass transfer speed, thereby improving the electrochemical carbon capture efficiency.

[0046] 2. Compared with the traditional catalytic electrode preparation process, the preparation process of the 3D printed catalytic electrode of the present invention is relatively simple, and an integrated catalytic electrode is obtained, which does not require the use of adhesives, conductive agents, etc. and can be directly used as a catalytic electrode.

[0047] 3. Compared with traditional electrode technology, the present invention, due to the advantages of its 3D printing preparation process, can not only achieve a more sophisticated customized electrode macrostructure through simpler steps, but also achieve the introduction of catalytic electrode active sites with higher degrees of freedom, making it easier to meet various application requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 The 3D printed body and 3D carbon-based catalytic electrode prepared by the present invention;

[0049] Figure 2 TEM images of the DIW-FePc-CE (a, b) with the best performance prepared by the present invention;

[0050] Figure 3 XRD spectrum of DIW-FePc-CE prepared in the present invention;

[0051] Figure 4 High-resolution XPS spectra of C1s (a), N 1s (b) and Fe 2p (c) of DIW-FePc-CE prepared in the present invention;

[0052] Figure 5 FEco and FE of the best DIW-FePc-CE prepared by the present invention at different voltages H2 (a); Stability test of DIW-FePc-CE sample at -0.7 V (b). DETAILED DESCRIPTION

[0053] The preparation and performance of the ink direct writing 3D printing electrode of the present invention are further described below through specific examples and comparative examples.

[0054] Example 1

[0055] (1) Preparation of ink direct writing ink: 10 g of gelatin was added to 10 ml of phosphate buffer with pH = 6.25, stirred at 50 ° C until completely dissolved, and then 5.8 ml of methacrylic anhydride was added as a cross-linking agent, and continued to stir at 40 ° C for 1 hour. Then, it was dialyzed with deionized water for 5 days and freeze-dried to obtain GeIMA. Then 0.5 g of GeIMA, 10 mg of photoinitiator, and 10 ml of water were mixed, and 1.0 g of gelatin was added thereto, and ultrasonicated at 40 ° C until completely dissolved to obtain 3D printing ink.

[0056] (2) Printing the electrode precursor component: According to the shape required in the electrocatalytic process, the 3D printing ink is 3D printed using the ink direct writing technology, and a needle with an inner diameter of 1.2 mm is selected to obtain a 3D printed body.

[0057] (3) Construction of carbon-based catalytic electrode: The 3D printed body was pre-carbonized and heated to 950°C in a tube furnace at a rate of 5°C / min, then kept at this temperature for 10 h, and finally cooled to room temperature at a rate of 10°C / min to obtain a 3D carbon-based electrode. The 3D carbon-based electrode was placed in a solution containing 7 g L -1 The 3D carbon-based catalytic electrode was obtained by immersing the 3D carbon-based catalytic electrode in a FePc solution for 4 hours and then performing a final carbonization treatment. In a tube furnace, the temperature was first increased to 950°C at a rate of 5°C / min, then kept constant for 10 hours, and finally decreased to room temperature at a rate of 10°C / min.

[0058] (4) Characterization of active electrodes: When the prepared 3D carbon-based catalytic electrode is used in the reaction of reducing carbon dioxide to carbon monoxide, the CO Faradaic efficiency can reach 60% at -0.7 V vs. RHE and remain stable for 20 h with good product selectivity.

[0059] Example 2

[0060] The final carbonization treatment temperature in step (3) was adjusted to 1000° C., and the other operations were the same as in Example 1 to obtain a 3D carbon-based catalytic electrode.

[0061] The activity of the prepared catalytic electrode was characterized: for the prepared 3D carbon-based catalytic electrode, when it was used in the reaction of reducing carbon dioxide to carbon monoxide, the CO Faraday efficiency could reach 40% at -0.7Vvs.RHE, and it maintained stability for 17h, and had good product selectivity.

[0062] Example 3

[0063] Adjust the concentration of the FePc solution soaked in step (3) to 10 g / L -1 , other operations were the same as in Example 1 to obtain a 3D carbon-based catalytic electrode.

[0064] The activity of the prepared catalytic electrode was characterized: for the prepared 3D carbon-based catalytic electrode, when it was used in the reaction of reducing carbon dioxide to carbon monoxide, the CO Faraday efficiency could reach 35% at -0.7Vvs.RHE, and it maintained stability for 17h, and had good product selectivity.

[0065] Example 4

[0066] The water temperature of the ultrasonic operation in step (1) was adjusted to 30° C. The other operations were the same as in Example 1 to obtain a 3D carbon-based catalytic electrode.

[0067] The activity of the prepared catalytic electrode was characterized: for the prepared 3D carbon-based catalytic electrode, when it was used in the reaction of reducing carbon dioxide to carbon monoxide, the CO Faraday efficiency could reach 33.5% at -0.7Vvs.RHE, and it maintained stability for 18 hours and had good product selectivity.

[0068] Comparative Example 1

[0069] The final carbonization treatment temperature in step (3) was adjusted to 1200° C., and the other operations were the same as in Example 1 to obtain a 3D carbon-based catalytic electrode.

[0070] The activity of the prepared catalytic electrode was characterized: for the prepared 3D carbon-based catalytic electrode, when it was used in the reaction of reducing carbon dioxide to carbon monoxide, the CO Faraday efficiency reached only 11% at -0.7Vvs.RHE.

[0071] This is due to the high temperature of the carbonization process, which will damage the carbon skeleton structure and adversely affect the formation of defects, thus affecting the catalytic electrode activity.

[0072] Comparative Example 2

[0073] Adjust step (3) to 4 gL -1 , other operations were the same as in Example 1 to obtain a 3D carbon-based catalytic electrode.

[0074] The activity of the prepared catalytic electrode was characterized: for the prepared 3D carbon-based catalytic electrode, when it was used in the reaction of reducing carbon dioxide to carbon monoxide, the CO Faraday efficiency reached only 10% at -0.7Vvs.RHE.

[0075] This is due to the low concentration of the FePc solution used for immersion. If the concentration of the active solution is too low, the active sites on the surface of the catalytic electrode will be insufficient, thus affecting the activity of the catalytic electrode.

[0076] Comparative Example 3

[0077] The temperature of the ultrasonic operation in step (1) was adjusted to 70° C., and other operations were the same as in Example 1. When preparing the 3D electrode, the electrode could not be formed.

[0078] This is caused by the water temperature being too high. If the water temperature is too high, the printing ink will not be viscous enough, which is not conducive to the formation of the printed body.

[0079] Comparative Example 4

[0080] The inner diameter of the needle tube used in step (2) was adjusted to 2.0 mm, and other operations were the same as in Example 1. The obtained 3D printed electrode did not achieve the target morphology.

[0081] This is because the inner diameter of the needle tube is too thick, resulting in the extruded ink bar being too thick, and the printed body collapses before it has time to be fixed.

Claims

1. A method for preparing Fe-NC carbon-based catalytic electrode by ink direct writing 3D printing technology, comprising the following steps: (1) Preparation of ink direct writing ink: gelatin is added to a buffer solution, and then a cross-linking agent is added, dialyzed, and freeze-dried to obtain GelMA, GelMA and a photoinitiator are mixed in water according to a certain proportion until they are completely dissolved, and then gelatin and the prepared sample are mixed in water according to a certain proportion, and a printable ink is prepared by ultrasonication, and stored in the dark; (2) Printing of 3D components: According to the shape required in the electrocatalytic process, under the relevant printing parameters, the printing ink is 3D printed by ink direct writing, and the printed body is freeze-dried for 15 to 25 hours to obtain a 3D printing precursor; (3) Preparation of Fe-NC carbon-based catalytic electrode: The 3D printed precursor is pre-carbonized and then immersed in a solution containing active substances for 3 to 5 hours for final carbonization to obtain a 3D printed carbon-based catalytic electrode.

2. A method for preparing Fe-NC carbon material catalytic electrode by ink direct writing 3D printing as claimed in claim 1, characterized in that: The buffer in step (1) is selected from one or more of phosphate buffer, glycine-hydrochloric acid buffer, phthalic acid-hydrochloric acid buffer, and the pH of the added buffer is between 6.00 and 6.50; the cross-linking agent in step (1) is one or more of diisopropylbenzene peroxide, methacrylic anhydride, and diisopropylbenzene hydroperoxide, and the amount of the cross-linking agent added is 0.05 to 0.80 times the mass of gelatin.

3. A method for preparing Fe-NC carbon material catalytic electrode by ink direct writing 3D printing as claimed in claim 1, characterized in that: The number of days required for ultrapure water dialysis in step (1) is 3 to 10 days, and the water is changed twice a day; the molecular weight cutoff of the dialysis bag used for ultrapure water dialysis in step (1) is between 1000 and 1500.

4. A method for preparing Fe-NC carbon material catalytic electrode by ink direct writing 3D printing as claimed in claim 1, characterized in that: The photoinitiator in step (1) is one or more of diphenylphosphine oxide, benzoin dimethyl ether, and triphenyl hexafluorophosphate hexachloride; the amount of the photoinitiator added in step (1) is 0.01 to 0.05 times that of GelMA.

5. A method for preparing Fe-NC carbon material catalytic electrode by ink direct writing 3D printing as claimed in claim 1, characterized in that: The temperature of water required during the ultrasonic process in step (1) is 25-40°C.

6. A method for preparing Fe-NC carbon material catalytic electrode by ink direct writing 3D printing as claimed in claim 1, characterized in that: The inner diameter of the needle of the ink direct writing printing device used in step (2) ranges from 1.05 mm to 1.3 mm.

7. A method for preparing Fe-NC carbon material catalytic electrode by ink direct writing 3D printing as claimed in claim 1, characterized in that: The pre-carbonization treatment process is as follows: in a tubular furnace, the temperature is first raised to 800-1000° C. at a rate of 1-10° C. / min, maintained at a constant temperature for 5-10 hours, and finally lowered to room temperature at a rate of 1-10° C. / min.

8. A method for preparing Fe-NC carbon material catalytic electrode by ink direct writing 3D printing as claimed in claim 1, characterized in that: The final carbonization treatment process is: in a tubular furnace, firstly heating to 800-1000° C. at a rate of 1-10° C. / min, maintaining the temperature for 5-10 hours, and finally cooling to room temperature at a rate of 1-10° C. / min.

9. A method for preparing Fe-NC carbon material catalytic electrode by ink direct writing 3D printing as claimed in claim 1, characterized in that: The active substance is one or more of iron phthalocyanine, iron acetylacetonate, and iron chloride, and the concentration of the solution is in the range of 7 to 10 g / L. -1 .

10. Use of the 3D printed carbon-based catalytic electrode as claimed in claim 1 in electrochemical carbon capture.